Engineering a cyanobacteriochrome two-component system into a synthetic, light-controlled gene expression system for plants - Hofmann, Roberto (Apollo - University of Cambridge Repository, 2023)
Our inability to perturb the expression of genes at cellular resolution in planta has hampered our investigation of spatial and temporal dynamics. Ideally, we would like an orthogonal, genetically encoded system, that allows us to reversibly perturb the expression of genes of interest with maximal spatiotemporal resolution in a minimally invasive way. Our lab has reengineered the CcaS/R light receptor two-component system from cyanobacterium Synechocystis sp. PCC 6803 into a plant-compatible synthetic light-controlled gene expression system called Highlighter. This system was initially deployed in transiently transformed *Nicotiana benthamiana* leaves. However, challenges remained: an incomplete mechanistic understanding of CcaS light sensing, light response spectra overlapping with plant light signalling pathways, low engineering throughput, and most importantly the inability to use the system in stably transformed plants. Highlighter exhibits a novel blue light response not observed in wild-type CcaS/R without an obvious biochemical basis. Here I describe the use of structural modelling, spectroscopy, genetics, and functional assays to investigate how CcaS responds to blue light. I demonstrate by targeted mutagenesis, domain deletions and domain swapping, that the blue-light response is due to a not previously characterised LOV-like domain. Next, I applied this insight to engineering new versions of the protein with improved light response kinetics. Further, I describe advances in engineering Highlighter to function in *Arabidopsis thaliana* and generate stable transgenics. I aim to target GA20OX1, a gibberellin (GA) synthesis gene with the aim of modifying GA patterns visualised by the FRET-based biosensor nlsGPS1 developed by our group. To speed up *in planta* testing of new Highlighter variants, I developed new visual assays and worked to identify optimal light conditions for widespread deployment. Finally, I attempted to deploy a light-controlled Cas9-based programmable transcription factor *in planta*, that has recently been developed for use in mammalian cells. I demonstrate the ability of the system to induce gene expression in planta in the first step to developing the system into a viable optogenetic system for use in plants.
Keywords: Light receptors; Optogenetics; Synthetic biology